Specific Features of Big Corporations Lobbying in the Political Dynamics of Global Megapolis (Case of the Housing Renovation Program in Moscow). Part 2 - A. A. Degtyarev; A. S. Potapkin (Сравнительная политика)
The second part of the article addresses the specific issues of the PJSC PIK’s lobbying activity and behavior in the context of the sectoral political and administrative dynamics in the megapolis of Moscow. This lobbying activity manifests itself in the transformational process of ‘conversion’ in which stakeholders harmonize an integral and complex ‘interest formula’ define public problems and formulate public agenda through the representation and promotion of particular interests, political influence of business organizations on the Moscow authorities in the field of construction policy. The study highlights five main phases of how private interests are converted and incorporated in the public agenda. The study utilizes case study as well as document analysis, non-participant observation and expert interview to analyze the dynamics and logic of PIK’s proactive participation in the lobbying promotion of the world’s largest housing redevelopment program.